Women Pre-Scripted Forging Modern Roles through Korean Print - Lee, Ji-Eun (University of Hawaii Press, 2015)
Women Pre-Scripted explores the way ideas about women and their social roles changed during Korea's transformation into a modern society. Drawing on a wide range of materials published in periodicals-ideological debates, cartoons, literary works, cover illustrations, letters and confessions--the author shows how at different times between 1896 and 1934, the idea of modern womanhood transforms from virgin savior to mother of the nation to manager of modern family life and, finally, to an embodiment of the capitalist West, fully armed with sexuality and glamour.Each chapter examines representative periodicals to explore how their content on a range of women's issues helped formulate and prescribe women's roles, defining what would later become appropriate knowledge for women in the new modern context. Lee shows how in various ways this prescribing was gendered, how it would sometimes promote the "modern" and at other times critique it. She offers a close look at primary sources not previously introduced in English, exploring the subject and genre of each work, the script used, and the way it categorized or defined a given women's issue. By identifying and dissecting the various agendas and agents behind the scenes, she is able to shed light on the complex and changing relationship between domesticity, gender, and modernity during Korea's transition to a modern state and its colonial occupation. Women Pre-Scripted contributes to the swell of research on Asian women in recent years and expands our picture of a complex period. It will be of interest to scholars of Korean literature and history, East Asian literature, and others interested in women and gender within the context of colonial modernity